To the issue of increasing the efficiency of the process of physical education of student youth - Vypasniak, Igor; Shankovsky, Andriy (Journal of Education, Health and Sport, 2017)
Topicality. A characteristic feature of the educational sphere of modern Ukraine is the presence of trends in the integration and modernization of higher education with regard to the world experience. Finding the best ways to train highly skilled professionals with a sufficient level of competitiveness in the labor market is the major challenge for the modern system of higher education. Objectives of the Study: using the method of expert assessments to determine the perspectives of increasing the efficiency of the process of physical education of students. Research results. The question of high interest for us and a large number of researchers in the sphere of physical education of students concerns the reasons of the low efficiency of the process of physical education of student youth. Experts draw attention to the lack of data processing in the sphere of education, especially in the process of physical education, and the first place was assigned to the problem of the absence of modern information and methodological systems that inform about the role of a healthy lifestyle under today’s social and economic conditions. The vast majority of experts draw attention to the need for the integrated application of information and telecommunication technologies in the process of physical education. Programs are to be implemented and should operate with the means of forming theoretical knowledge and the ability to control the level of their assimilation. The overwhelming number of experts noted the need to form students’ theoretical knowledge about the forms, means and methods of body composition correction, as well as the correction of disorders of the locomotor apparatus in the process of physical education. Conclusions. The guidelines for increasing the efficiency of the process of physical education of student youth are determined.